Living arrangements and food security of a sample of older Palestinian refugees in Lebanon - Nadine R. Sahyoun; Anniebelle Sassine; Anna Vaudin; Fayrouz Sakr-Ashour; Hala Ghattas (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Although we know of the relationship between food insecurity, poor dietary intake and health outcomes, there are limited studies examining the determinants of food insecurity in older adults in developing countries. This study describes the living arrangement and characteristics of protracted Palestinian refugees in Lebanon aged 60 years and older and, the status and determinants of household food insecurity. # Methods Two surveys, representative of Palestinian refugees in Lebanon (2010 and 2015), were appended and used to examine living arrangement of older adults and household food security. Our final pooled sample included 5412 households and 24,540 individuals. Of these individuals, 10.85% (n=2663) were adults aged 60 years and older, our population of interest. Living arrangement included 1) households with no older adults, 2) multigenerational households that included at least one older adult, 3) older adults living alone, with spouse or with another older person (single households). Food security was collected using two similar questionnaires that were equated and scores were used to classify households into food secure, moderately and severely food insecure. Means and proportions were used to examine household characteristics and sociodemographic and health variables of older adults by living arrangements. Logistic regression tested determinants of food insecurity. # Results About 27% of older adults lived in single households and of those living alone, 94.3% were women. Overall, poverty was highly prevalent in households (57%) and only 38% of households were food secure. However, poverty and food insecurity were significantly less prevalent in single households (P<0.0001) and these were also the highest recipients of welfare and remittances. # Conclusions Successful interventions to address poverty and food insecurity will require a better understanding of family structure, interactions within the household, and the role that older adults play within the family.